Leading, following or complementing in economic crisis: A conceptual model illustrating nonprofit relationships with public schools - Laurie Paarlberg; Rebecca Nesbit; Richard Clerkin; Robert Christensen (Administrative Sciences, 2014)
Public and nonprofit organizations, entwined in the delivery of public goods and services, are in the midst of challenging economic times. In these circumstances, sound collaborative leadership may help bridge budget and program service delivery shortfalls. In this paper, we examine the administrative dynamics of mutual reliance between two prominent public and nonprofit organizations: public schools and parent-teacher groups (PTGs). We conclude that the partnership is changing as a result of external, economic forces. In essence, we are seeing a threat-rigidity response. The economic crisis may be responsible for causing PTGs to narrow their range of activities away from broader strategic issues that can be addressed through their confrontation activities and advocacy mission towards a narrower focus on classroom activities that protect core school operations, namely instruction.
Keywords: 350; nonprofit leadership; collaboration; schools; parent teacher organizations; groups